Investigation of exact soliton solutions of nematicons in liquid crystals according to nonlinearity conditions - Durur, Hulya; Yokus, Asif; Duran, Serbay (World Scientific Publ Co Pte Ltd, 2024)
In this work, new traveling wave solutions are generated for the system that models nematicons in liquid crystals using the (1/G')-expansion method. In the equation system, nonlinearity is taken into account for Kerr law and Power law. Also, the existence of exact solutions under restriction conditions is guaranteed. We suggest that the solutions produced are of a different type than the solutions in the literature. Figures representing the intensity of the produced traveling wave solutions are presented. In addition, the simulation of the solitary wave is made for different values of the parameter that affects the inclination angle of the molecules in the nematicons mechanism in liquid crystals. How classical solitary wave behavior translates into triangular wave behavior is discussed. We believe this paper will provide an important perspective on the problems encountered in various application areas such as fluid dynamics, chemical engineering, chaos and complex networks in terms of investigating different mechanisms by taking into account nonlinearity factors.
Keywords: Nematicons; liquid crystals; Kerr and Power Law; (1/G')-expansion method